A Portable Droplet Magnetofluidic Device for Point-of-Care Detection of Multidrug-Resistant Candida auris - Lee, Pei-Wei; Totten, Marissa; Chen, Liben; Chen, Fan-En; Trick, Alexander Y.; Shah, Kushagra; Ngo, Hoan Thanh; Jin, Mei; Hsieh, Kuangwen; Zhang, Sean X.; Wang, Tza-Huei (Frontiers in Bioengineering and Biotechnology, 2022)
Candida auris is an emerging multi-drug resistant fungal pathogen that can cause severe and deadly infections. To date, C. auris has spurred outbreaks in healthcare settings in 33 countries across 5 continents. To control and potentially prevent its spread, there is an urgent need for point-of-care (POC) diagnostics that can rapidly screen patients, close patient contacts, and surveil environmental sources. Droplet magnetofluidics (DM), which leverages nucleic acid-binding magnetic beads for realizing POC-amenable nucleic acid detection platforms, offers a promising solution. Herein, we report the first DM device – coined POC.auris – for POC detection of C. auris. As part of POC.auris, we have incorporated a handheld cell lysis module that lyses C. auris cells with ~2 min hands-on time. Subsequently, within the palm-sized and automated DM device, C. auris and control DNA are magnetically extracted and purified by a motorized magnetic arm and finally amplified via a duplex real-time quantitative PCR assay by a miniaturized rapid PCR module and a miniaturized fluorescence detector – all in ≤ 30 min. For demonstration, we use POC.auris to detect clinically isolated C. auris from 3 major clades, with no cross-reactivity against other Candida species and a limit of detection of ~300 colony forming units per mL. Taken together, POC.auris presents a potentially useful tool for combating C. auris.